(untitled) (Metallurgy and Foundry Engineering, 2005)
Low-alloy Cr-Mn-Ni-Mo cast steels and high-alloy manganese cast steels are frequently use as castings in such areas as mineral industry and power industry. Melting technology of these steels is often based on the use the return-scrap in charge, because the prices of nickel and molybdenum are very high. Basic eleetric are furnaces were used in the oxidation remelting of high manganese and Iow alloyed Cr-Mn-Ni-Mo steel scraps. The measuring of bath temperature and chemical eomposition were realized for control of C, P and Cr oxidation rates. This article shows effect of two methods of carbon boil, used in remelting technology: first is carbon oxydation by iron ore and second is oxygen-blowing. The results of these measurements showed that at the oxygen blowing under the pressure of ca 0,6-0,8 MPa and oxygen capacity of 0,37-0,60 Nm3/(min·Mg), the average value of decarburisation rate is 1,03-2,08% C/h, according the temperature of the bath. In the same condition of oxidation, the dephosphorisation rate in Cr-Mn-Ni-Mo is 0-0,12% P/h. It was shown that the temperatures above 1620 degrees C protected steel bath against high chromium losses. At these temperatures the average value of phosphor oxidation rate is 0,070% P/hour.